2022
DOI: 10.1007/s00068-022-01933-y
|View full text |Cite
|
Sign up to set email alerts
|

The grade of instability in fragility fractures of the pelvis correlates with impaired early mobilization

Abstract: Purpose This study aimed to investigate whether gait patterns of patients with fragility fractures of the pelvis (FFP) comply with the grade of fracture instability, defined by radiological patterns. Patients and methods This prospective, single-center, observational study included 39 patients with an FFP. Gait analysis was performed with a wearable insole force sensor (Loadsol® by Novel, Munich, Germany) 4–7 days after admission. Patients were divided in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Also, the largest number of patients suffered from an FFP type II (50%), while patients with an FFP type III (0%) were not present. This distribution was, however, also noted in other studies [ 16 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Also, the largest number of patients suffered from an FFP type II (50%), while patients with an FFP type III (0%) were not present. This distribution was, however, also noted in other studies [ 16 ].…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, the aim of this study was to compare pre- and postoperative mobilization after surgical treatment of FFP types II, III and IV with the iFuse using sensor-supported insoles (Loadsols ® , Novel, Munich, Germany). Previous studies have already demonstrated the effectiveness of sensor-supported insoles for the detection of compromised mobility [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%